Building a foundation to study distributed information behaviour - Terry L. von Thaden (Information Research: An International Electronic Journal)
Introduction. The purpose of this research is to assess information behaviour as it pertains to operational teams in dynamic safety critical operations. Method. In this paper, I describe some of the problems faced by crews on modern flight decks and suggest a framework modelled on Information Science, Human Factors, and Activity Theory research to assess the distribution of information actions, namely information identification, gathering and use, by teams of users in a dynamic, safety critical environment. Analysis. By analysing the information behaviour of crews who have accidents and those who do not, researchers may be able to ascertain how they (fail to) make use of essential, safety critical information in their information environment. The ultimate goal of this research is to differentiate information behaviour among the distinct outcomes. Results. This research affords the possibility to discern differences in distributed information behaviour illustrating that crews who err to the point of an accident appear to practice different distributed information behaviour than those who do not. This foundation serves to operationalise team sense-making through illustrating the social practice of information structuring within the activity of the work environment. Conclusion. . The distributed information behaviour framework provides a useful structure to study the patterning and organization of information distributed over space and time, to reach a common goal. This framework may allow researchers and investigators alike to identify critical information activity in the negotiation of meaning in high reliability safety critical work, eventually informing safer practice. This framework is applicable to other domains.